B419 Patient outcomes following hip fracture surgery using intrathecal 2% prilocaine alongside peripheral nerve blocks. (11th August 2022) - Sathyanarayana, A; Phang, G; Gorecha, M; Dasgupta, K
Abstract : Background and Aims: Regional anaesthesia has increasingly become the mode of anaesthesia for hip fractures in view of the frail, elderly multiple comorbid populations who usually succumb to this significant injury. Bupivacaine is often the choice for spinal anaesthesia however, local anaesthetics like 2% Prilocaine (Prilotekal®) are gaining popularity in recent years due to their fast offset and better side effects profile. We analysed patient outcomes using intrathecal Prilocaine alongside peripheral nerve blocks and Eleveld modelled target-controlled infusion (TCI) 1% Propofol for sedation. Ethical committee approval was deemed unnecessary by our audit and research department as patients receive short-acting spinal anaesthesia with blocks routinely. Methods: Data from 84 patients who received intrathecal 2% Prilocaine alongside ultrasound-guided peripheral nerve blocks (Femoral and Lateral cutaneous nerve of thigh) and Elevled TCI Propofol sedation were analysed. We recorded the day 1 post-op systolic blood pressure, pre and post-operative pain score, length of stay and 30-day mortality. Results: We noted that no patient required additional analgesia in recovery, no admissions to intensive care and 30-day mortality was found to be 4%, which is better than the UK national average. The mean length of stay in the hospital was found to be 18 days. Conclusions: We observed that intrathecal Prilocaine combined with nerve blocks is a reliable technique in hip fracture surgery, offers haemodynamic stability and could improve overall survival. Further study of the use of short-acting intrathecal agents is required in comparison to traditional methods.